Hemodynamic Evaluation of Avalon Elite Bi‐Caval Dual Lumen Cannulas and Femoral Arterial Cannulas. Issue 1 (1st October 2018) - Wang, Shigang; Force, Madison; Kunselman, Allen R.; Palanzo, David; Brehm, Christoph; Ündar, Akif
Abstract: Translational research is a useful tool to provide scientific evidence for cannula selection during extracorporeal life support (ECLS). The objective of this study was to evaluate four Avalon Elite bi‐caval dual lumen cannulas and nine femoral arterial cannulas in terms of flow range, circuit pressure, pressure drop, and hemodynamic energy transmission in a simulated adult ECLS model. A veno‐venous ECLS circuit was used to evaluate four Avalon Elite bi‐caval dual lumen cannulas (20, 23, 27, and 31 Fr), and a veno‐arterial ECLS circuit was used to evaluate nine femoral arterial cannulas (15, 17, 19, 21, and 23 Fr). The two circuits included a Rotaflow centrifugal pump, a Quadrox‐D adult oxygenator, and 3/8 in ID tubing for arterial and venous lines. The circuits were primed with lactated Ringer's solution and packed human red blood cells (hematocrit 40%). Trials were conducted at rotational speeds from 1000 to 5000 RPM (250 rpm increments) for each Avalon cannula, and at different flow rates (0.5–7 L/min) for each femoral arterial cannula. Real‐time pressure and flow data were recorded for analysis. Small caliber cannulas created higher circuit pressures, higher pressure drops and higher M ‐numbers compared with large ones. The inflow side of Avalon dual lumen cannula had a significantly higher pressure drop than the outflow side (inflow vs. outflow: 20 Fr‐100.2 vs. 49.2 mm Hg at 1.1 L/min, 23 Fr‐93.7 vs. 41.4 mm Hg at 1.6 L/min, 27 Fr‐102.3 vs. 42.8 mm Hg at 2.6 L/min, 31 Fr‐98.1 vs. 44.7 mm Hg at 3.8 L/min). There was more hemodynamic energy lost in the veno‐arterial ECLS circuit using small cannulas compared to larger ones (17 Fr vs. 19 Fr vs. 21 Fr at 4 L/min—Medtronic: 71.0 vs. 64.8 vs. 60.9%; Maquet: 71.4 vs. 65.6 vs. 62.0%). Medtronic femoral arterial cannulas had lower pressure drops (Medtronic vs. Maquet at 4 L/min: 17 Fr‐121.7 vs. 125.0 mm Hg, 19 Fr‐71.2 vs. 73.7 mm Hg, 21 Fr‐42.9 vs. 47.4 mm Hg) and hemodynamic energy losses (Medtronic vs. Maquet at 4 L/min: 17 Fr‐43.6 vs. 44.4%, 19 Fr‐31.0 vs. 31.4%, 21 Fr‐20.8 vs. 22.4%) at high flow rates when compared with the Maquet cannulae. The results for this study provided valuable hemodynamic characteristics of all evaluated adult cannulas with human blood in order to guide ECLS cannula selection in clinical practice. Use of larger cannulas are suggested for VV‐ and VA‐ECLS.